EDMODO IN ENGLISH LANGUAGE LEARNING: A REVIEW OF RECENT STUDIES - Azizatul Mahfida Mahfida Inayati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
ABSTRACTMany dynamic approaches have emerged due to computer technology infacilitating language learning. The use of Computer Assisted Language Learningin the teaching and learning becomes essential. Learning platform is used in thelearning process as a tool that is considered capable of attracting students’attention and increasing their motivation. It is then that underlies the number ofresearchers who are interested to raise the theme into the realm of both theoreticaland empirical research. This study reviewed fourteen journal articles to determinethe effect of presentation software, initially focused on Edmodo which is a freeand secure learning platform which is free of advertisements, games and otherdistractions used to provide a simple way for teachers to create and manageonline classroom, and enable students to connect with teacher and other studentsanywhere and anytime. Eight of them are empirical and others are theoretical.The constant comparative method proposed by Lincoln and Gub (1985) used toanalyse each article. As the results, this study found that learning platform,especially Edmodo, greatly support teaching and learning activities. It will bevery helpful for every person in the field of education such as students, teachers,and researchers in order to adopt this innovative technology for language learningand teaching.Keywords: Edmodo, learning platform, pedagogy